KARAKTERISTIK PENDERITA MENINGOENSEFALITIS RAWAT INAP DI RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2007-2011 - Ristari Malau (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2012)
Meningoencephalitis is one of infection disease still become a problem in developing country. The number of patients with meningoencephalitis were hospitalized in Santa Elisabeth Medan in 2007-2011 was 120 patients. The purpose of this descriptive study with case series design is to analyse the characteristic of the patient with meningoencephalitis were hospitalized in Santa Elisabeth Medan in 2007-2011. The population for this study was 120 patients. Data analysed by using Chi-square, Mann-whitney, Kruskal Wallis. The highest proportion of patient with meningoencephalitis in the age group 0-5 years old 53,4%, male 28,4% and female 25,0%; ethnic Batak 77,5%, Christian  57,5%; doesn’t work 56,6%; from out of Medan 53,3%; somnolen 25,8%; fever of age <5 years 96,6%; fever of age ≥5 years 90,2%; letarghy 72,5%; the average length of treatment was 5,72 days; The result of Chi-Square, there were no significant differences between the arrival condition by their home (p=0,493); the average length of treatment significance was more length in compos mentis arrival condition compared with incompos mentis arrival condition (p=0,021), the average length of treatment significance was more length for home healthy/home treatment than back home by own request, death patient, and leave of hospital (p=0,000) It is suggested that the management of Santa Elisabeth Hospital Medan to complete the filling out patient’s status card by including home treatment, and to mother who has child 0-<5 years old suggested to give an imunnization to their child, and immediately checked out when have the symptons of fever, convulsions and letarghy. Key words: Meningoencephalitis, the characteristics of patients